2022
DOI: 10.1109/tit.2022.3158868
|View full text |Cite
|
Sign up to set email alerts
|

Secure Distributed Matrix Computation With Discrete Fourier Transform

Abstract: We consider the problem of secure distributed matrix computation (SDMC), where a user queries a function of data matrices generated at distributed source nodes. We assume the availability of N honest but curious computation servers, which are connected to the sources, the user, and each other through orthogonal and reliable communication links. Our goal is to minimize the amount of data that must be transmitted from the sources to the servers, called the upload cost, while guaranteeing that no T colluding serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Both traditional SSMM and SMBMM mainly focus on the special case that the matrices A and B have the same security level (i.e., X = X A = X B ). For SSMM, the state of the art are reflected in Secure Generalized PolyDot (S-GPD) codes [1], GASP codes [6], A3S codes [13], USCSA codes [14], FFT-based Polynomial (FFT-P) codes [18], Polynomial Sharing (PS) codes [19] and Extended Entangled Polynomial (E-EP) codes [33]. Depending on the partitioning manners of the data matrices, these works are divided into two classes of row-by-column partition [6], [13], [14] (where the partitioning parameter p is set to be 1 and m, n are arbitrary) and arbitrary partition [1], [18], [19], [33] (where all the partitioning parameters m, p, n are arbitrary).…”
Section: Performance Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both traditional SSMM and SMBMM mainly focus on the special case that the matrices A and B have the same security level (i.e., X = X A = X B ). For SSMM, the state of the art are reflected in Secure Generalized PolyDot (S-GPD) codes [1], GASP codes [6], A3S codes [13], USCSA codes [14], FFT-based Polynomial (FFT-P) codes [18], Polynomial Sharing (PS) codes [19] and Extended Entangled Polynomial (E-EP) codes [33]. Depending on the partitioning manners of the data matrices, these works are divided into two classes of row-by-column partition [6], [13], [14] (where the partitioning parameter p is set to be 1 and m, n are arbitrary) and arbitrary partition [1], [18], [19], [33] (where all the partitioning parameters m, p, n are arbitrary).…”
Section: Performance Comparisonsmentioning
confidence: 99%
“…The problem of secure DMM was first launched by Tandon et al in [2] for Single Secure Matrix Multiplication (SSMM), which is shown to achieve the optimal download cost for one-sided SSMM (where only one of the data matrices is kept secure). Subsequently, many works [1], [6], [13], [14], [18], [19], [20], [30] focus on two-sided SSMM (both matrices are kept secure).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SDMM was first introduced by Chang and Tandon in [1]. Many different schemes have since been presented, such as the secure MatDot scheme in [2], the GASP scheme in [3] and the DFT scheme in [4]. These schemes compute the products over finite fields, but computations over complex numbers have also been considered in [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%